Sensory Processing Difficulties Correlate With Disease Severity and Quality of Life Among Children With Migraine - Genizi, Jacob; Halevy, Ayelet; Schertz, Mitchell; Osman, Khaled; Assaf, Nurit; Segal, Idan; Srugo, Isaac; Kessel, Aharon; Engel-Yeger, Batya (Frontiers in Neurology, 2019)
Introduction: Headaches are common among children and about 80% of children reporting them. Migraine and tension type headaches are the most common primary headaches in children and the prevalence of migraine is about 8%. Accompanying sensory symptoms are common before, during and after migraine attacks. They may be a part of a wider symptom constellation called sensory processing disorder or difficulties (SPD). This includes both hyper or hypo sensitivity to sensations. However, the literature regarding sensory processing symptoms of children and youth with headaches as well as its interaction with child's emotional aspects and quality of life is scarce. Materials and Methods: 134 children between the ages of 8 and 12 participated in this study. 54 children (22 boys and 32 girls) with episodic migraine were prospectively recruited from pediatric neurological clinics during the years 2014-2017. The control group included 80 healthy children. Both groups completed a health and demographic questionnaire, headache assessment including Ped-MIDAS, Short Sensory Profile, State-Trait Anxiety Inventory (STAI) for children, and the Pediatric Quality of Life Inventory. Results: Children with migraine showed significantly higher prevalence of sensory processing difficulties and lower quality of life compared to healthy controls. Among children with migraine, sensory processing difficulties significantly correlated with lower quality of life. Headache-related disability and sensory processing difficulties predicted quality of life. Conclusion: The possible relationship between migraine and sensory processing disorder or difficulties stresses the need to screen for sensory processing difficulties among children with migraine and when found – refer to their impacts on children’s daily function and quality of life.